Heuristics as a learning methodology in processes in the sales area in ecuadorian commercial companies. - Yagual Velastegui, Alfredo Marcel; Coronel Pérez, Iván Ariolfo; Ortiz Luzuriaga, Daniel (Revista Universidad de Guayaquil, 2019)
The present article intends to analyze heuristics as a learning methodology in sales processes in commercial companies. That is, as a method of research and evaluation, in order to design and execute a learning methodology. For this, the methodology instruments were contrasted with heuristic criteria as a means of resolving conflicts of a company in the sales area. After a documentary analysis it was possible to conclude that they are a series of cognitive stages in teaching-learning that allow collaborators and managers to interpret the changes of environments that companies face on a day-to-day basis.